Political orthodoxies : the unorthodoxies of the Church coerced - Hovorun, Cyril (Dispatches (Minneapolis, Minn.), 2018)
Hovorun outlines forms of political orthodoxy in Orthodox churches, past and present and draws a big picture of religion being politicized and even weaponized. Political Orthodoxies focuses on the theological underpinnings of the culture wars waged in eastern and southern Europe. He explains the aggressive behavior of Russia toward its neighbors and the West from a religious standpoint. Following his analysis, Hovorun suggests ways to bring political Orthodoxy back to the apostolic and patristic track.